From left to right: Hilferding, Minna Ledebour, Minna K., Luise K., Anna Pannekoek, Mrs. Block, Georg Ledebour, Anton Pannekoek with son. Kneeling: KarlK., Hans Block, Mathilde Wurm. Lying: Benedikt K. and children Block
From left to right: Hilferding, Minna Ledebour, Minna K., Luise K., Anna Pannekoek, Mrs. Block, Georg Ledebour, Anton Pannekoek with son. Kneeling: KarlK., Hans Block, Mathilde Wurm. Lying: Benedikt K. and children Block.